ANALYSIS OF THE IMPLEMENTATION OF THE FAMILY HOPE PROGRAM (PKH) ON HANDLING STUNTING IN MOTHERS WHO HAVE CHILDREN AGED 12-23 MONTHS IN KRUENG SABEE SUB-DISTRICT, ACEH JAYA DISTRICT - Humaira, Humaira; Kala, Pasyamei Rembune (Transpublika Publisher, 2023)
Stunting is a significant nutritional challenge among toddlers worldwide. One government strategy to address stunting and improve public health, particularly for children, is the Family Hope Program (PKH). Introduced in 2007, PKH is a conditional social assistance program targeting Extremely Poor Households (EPHs). This program provides cash assistance to pregnant women, toddlers, preschoolers, the elderly, and individuals with disabilities. This research employs a qualitative descriptive approach to provide an in-depth and comprehensive understanding of the situation and phenomenon under study. Findings indicate that program participants receive PKH assistance for various health-related needs, including prenatal care for pregnant women and educational support for school-aged children. Additionally, assistance is provided to the elderly and disabled. It is recommended that the government enhance preventive measures for the community, especially for residents in remote areas and individuals with limited understanding of health's importance.